The design of extrusion screws : an optimization approach - Gaspar-Cunha, A. (2001)
The design of a screw for plasticating polymer extrusion based on scientific principles is still a challenging task, which has received surprisingly little attention in the literature. In the present work the design of a screw is considered as an optimization problem. The corresponding design methodology is discussed. Two alternative approaches are considered. In the first case, the aim is to maximize the value of an objective function that describes quantitatively the process performance in terms of pre-selected important process criteria. A multiobjective optimization scheme resorting to the use of optimal or non-dominated Pareto frontiers is also implemented, where the set of feasible individual solutions in terms of the various criteria is correlated, thus evidencing the compromise between them. The relevance of the solutions and the sensitivity of the method to changes in the criteria considered are demonstrated with a case study.